Conversion of Mild Cognitive Impairment to Alzheimer’s Disease in Monolingual and Bilingual Patients - Berkes, Matthias (Alzheimer Dis Assoc Disord, 2020)
PURPOSE: Conversion rates from mild cognitive impairment (MCI) to Alzheimer’ Disease (AD) were examined considering bilingualism as a measure of cognitive reserve. METHODS: Older adult bilingual (n = 75) and monolingual (n = 83) patients attending a memory clinic who were diagnosed with MCI were evaluated for conversion to AD. Age of MCI and AD diagnoses and time to convert were recorded and compared across language groups. PATIENTS: Patients were consecutive patients diagnosed with MCI at a hospital memory clinic. RESULTS: Bilingual patients were diagnosed with MCI at a later age than monolingual patients (77.8 years and 75.5 years, respectively), a difference that was significant in some analyses. However, bilingual patients converted faster from MCI to AD than monolingual patients (1.8 years and 2.8 years, respectively) resulting in no language group difference in age of AD diagnosis. This relationship held after accounting for education, cognitive level, immigration status, and sex. DISCUSSION: The findings suggest that greater cognitive reserve as measured by language status leads to faster conversion between MCI and AD, all else being equal.